A survey based study on factors effecting communication in GSD - Khan, A.A. (2014)
Presently, most of software development companies are trying to globalize their work throughout the world in order to get the various benefits. The phenomenon of this software globalization is called Global Software Development (GSD). However, GSD is not a simple job and the software companies face various challenges. In GSD Communication is a main issue and it became more complicated during Requirements Change Management (RCM). This research will result to explore different factors that can negatively affect communication during the RCM process by conducting a survey in GSD industry. A framework is proposed for the factors effecting communication and total nine hypotheses are developed. A quantitative research method has been used to collect and analyse the data. The results show that total seven out of nine hypotheses are supported and two hypotheses are rejected. Â© 2014 Maxwell Scientific Organization.